Colloidal Synthesis and Optical Properties of Cs2CuCl4 Nanocrystals - Wanying Gu; Yicheng Zeng; Yuan Deng; Pan Huang; Geyu Jin; Fangze Liu; Jing Wei; Hongbo Li (Crystals, 2023)
Lead-free copper halide perovskite nanocrystals (NCs) are emerging materials with excellent photoelectric properties. Herein, we present a colloidal synthesis route for orthorhombic Cs2CuCl4 NCs with a well-defined cubic shape and an average diameter of 24 ± 2.1 nm. The Cs2CuCl4 NCs exhibited bright, deep blue photoluminescence, which was attributed to the Cu(II) defects. In addition, passivating the Cs2CuCl4 NCs by Ag+ could effectively improve the photoluminescence quantum yield (PLQY) and environmental stability.